Beliefs about third-hand tobacco smoke among university employees: a cross-sectional study - Timarci, Ilgin; Banu Babaoğlu, Asya; Tözün, Mustafa; Sözmen, Kaan (Central European journal of public health, 2025)
OBJECTIVES: This study aimed to evaluate the beliefs about third-hand tobacco smoke (THS) among administrative and academic staff at a university. THS is a residual pollutant from tobacco smoke that lingers on surfaces and poses health risks, particularly to children. The study also aimed to understand these beliefs in relation to socio-demographic factors. METHODS: A cross-sectional survey was conducted with 332 university employees aged 18 and over. Data were collected between September and December 2023 through face-to-face and online questionnaires. The survey included the Beliefs About Third-hand Smoke (BATHS-T) Scale and questions on socio-demographic characteristics, second-hand smoke exposure, and attitudes towards a smoke-free campus. Beliefs About Third-hand Smoke Scale total and sub-dimension scores increase, it is understood that the participant's belief in the negative effects of third-hand tobacco exposure on persistence and health increases. RESULTS: The average age of participants was 36.1 years, with 38.3% being administrative personnel and 61.7% academic personnel. About 40.5% of the participants used tobacco products. The mean total BATHS-T score was 35.6, with health and persistence subscale scores averaging 19.9 and 15.7, respectively. Non-smokers had significantly higher BATHS-T scores than smokers. The participants with children scored higher on the health sub-dimension. Additionally, 78.9% supported a smoke-free campus, and those supporting it had higher BATHS-T scores. Awareness of the harms of second-hand smoke correlated with higher BATHS-T scores. CONCLUSION: The study highlights that non-smokers and those with children are more aware of THS risks. There is strong support for a smoke-free campus among university staff. The findings suggest a need for increased education on THS, especially targeted at smokers and those without children. Universities can play a crucial role in promoting smoke-free environments and raising awareness about the health risks associated with THS.
Keywords: Young Adult; Cross-Sectional Studies; Male; passive smoking; Health Knowledge, Attitudes, Practice; mladý dospělý; health awareness; Adult; dospělí; mužské pohlaví; průzkumy a dotazníky; znečištění tabákovým kouřem; Tobacco Smoke Pollution; lidé; ženské pohlaví; zdraví - znalosti, postoje, praxe; Humans; průřezové studie; environmental tobacco smoke pollution; Universities; univerzity; Female; Surveys and Questionnaires; university; lidé středního věku; smoke-free policy; Middle Aged